Eco-theology as a form of Christian diakonia to creation - Naumowicz, Cezary (Studia Ecologiae et Bioethicae, 2009)
Jürgen Moltmann, one of the world’s leading Protestant theologians, is widely recognized as a key figure in the growing concern for eco-theology. For Moltmann, the present ecological crisis can be overcome by a new understanding of God and creation. The concept of a triune God helps to dispel the myth of our unilateral relationship of dominion over nature. Moltmann sees also some positive aspects of Gaia theory. He champions a commitment to justice for all creatures, not just human. He moves beyond anthropocentrism and tries to balance the traditional emphasis on God’s creative work by insisting that a doctrine of creation should culminate in the Sabbath celebration.